1. To solve the exercise shown, you must expand the equation.
2. Accordind the the square of a sum, you have:
3. Therefore, you have the equation in standard form:
y = x²+2x-4
We have given an equation which is in vertex form.
y = (x+1)²-5
We have to convert above equation into standard form.
Standard form of equation is
y = ax²+bx+c
Expanding the square term by using following formula,
(a+b)² = a²+2ab+b²
Now, y = x²+2x+1-5
Adding like terms , we have
y = x²+2x-4 which is the answer.
your answer is the last one
divide the length of a'c' by the length of ac to get a scale factor of two
& then reflect vertically (over the y-axis)
so your answer is dilation by a scale factor of 2 followed by reflection over the y-axis
+ _ - _...